Phenomenology of the sick body - Ferreira, Rafael (Geografares, 2021)
The reflections of this article are based on an experience and an own experience. It deals with a sick body and its perceptual modifications. The lived body is primordial, and from it, we constitute our horizons of orientation: it is the zero point of orientation. So, what are the perceptual changes that a sick body promotes to the lived experience? In order to reflect on this issue, I use, especially, the phenomenology of Edmund Husserl regarding the problem of the constitution of corporeality (Leiblichkeit). Therefore, I will consider that a sick body causes not only a perceptual change, but above all, a disorientation.